2007
DOI: 10.1159/000102938
|View full text |Cite
|
Sign up to set email alerts
|

Postural Sway during Dual Tasks in Young and Elderly Adults

Abstract: Background: Previous studies have shown that healthy young adults are able to decrease their standing postural sway when an additional postural visual task, such as reading, is performed. Objective: In this study, we investigated postural sway during dual tasks in young and elderly adults. Methods: Twelve healthy active elderly adults (aged 65–75 years) and 12 healthy young adults (aged 22–39 years) participated in the study. The subjects performed different visual tasks while standing on a force plate. We var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
108
4
16

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 47 publications
14
108
4
16
Order By: Relevance
“…Deviating neural resources that are intended for postural control can entail a reduction in postural stability and increased range of mass center oscillations (23,24,25,26). In our study, increased co-contraction was found in the DMT gait condition between the VM and BF muscles when the dual task was implemented.…”
Section: Resultssupporting
confidence: 45%
“…Deviating neural resources that are intended for postural control can entail a reduction in postural stability and increased range of mass center oscillations (23,24,25,26). In our study, increased co-contraction was found in the DMT gait condition between the VM and BF muscles when the dual task was implemented.…”
Section: Resultssupporting
confidence: 45%
“…To standardize participant stance position, the platform was marked with a 2-cm width tape to indicate the desired positioning of the feet. Participants were asked to keep their sight fixed at a mark on the wall positioned 1.5 m away from the platform and 1.5 m above floor level (Prado et al 2007;Duarte and Freitas 2010) and to breathe normally. Participants were on barefoot and were instructed to stand for 30 s on the force platform, with arms relaxed and with minimal body sway.…”
Section: Static and Dynamic Balancementioning
confidence: 99%
“…Generally, this point is represented by a fixed target placed at the height of the participants' eyes. The distance between the eyes and the visual field seems to affect the postural stability [25][26][27] , and some care must be taken when selecting the distance between the participant and the visual field (generally about 1 meter). For example, young adults and elderly individuals reduced their sway when the visual target was 40 cm distant from them, compared to a distance of 3 meters 27 .…”
Section: Posturography Standardizationmentioning
confidence: 99%
“…The distance between the eyes and the visual field seems to affect the postural stability [25][26][27] , and some care must be taken when selecting the distance between the participant and the visual field (generally about 1 meter). For example, young adults and elderly individuals reduced their sway when the visual target was 40 cm distant from them, compared to a distance of 3 meters 27 . Other factors such as visual acuity, luminosity, location, and the size of the stimulus inside the visual field may also interfere with posture stability.…”
Section: Posturography Standardizationmentioning
confidence: 99%